Extramedullary Manifestations of Chronic Myelomonocytic Leukemia: Do We Treat like an Acute Myeloid Leukemia? - Prasun Pudasainee; Bimatshu Pyakuryal; Yogesh Subedi; Jenisha Upadhyay; Subarna Adhikari (Case Reports in Hematology)
Chronic myelomonocytic leukemia (CMML) is a relatively rare clonal hematologic disorder with features of myelodysplastic syndrome and myeloproliferative disease. Extramedullary leukemic involvement is rarely a presenting feature of CMML. As there are no clear guidelines in regard to the treatment of patients with extramedullary manifestations, its management is challenging. In this report, we discuss the management of our patient who presented with submandibular lymphadenopathy and gingivitis and was diagnosed with CMML.